การเตรียมฟิล์มยางธรรมชาติที่มีสภาพไม่ชอบน้ำสูงโดยการกราฟต์ด้วยมอนอเมอร์ออร์กาโนซิลิกอน - พัชรรุจี งามดี (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
The highly hydrophobic NR film could be prepared via surface modification by hydroxylation and then grafting with organosilicon monomers. After preparing the vulcanized natural rubber films (VNR), their surface was modified via hydroxylation to obtain hydroxylated natural rubber films (VNROH). The hydroxyl group (-OH) was expected to be active sites for grafting with organosilicon monomers via hydrolysis and polycondensation. The effects of acid types and their concentrations including the immersion time of VNR in the acid solutions on the amount of -OH group in the prepared VNR-OH films were monitored. It was found that the immersion of VNR films in the 75 wt% sulfuric acid solution for 1 h gave VNR-OH films with highest -OH content at 7.83 mol%. For the hydrophobicity analysis, the water contact angle of VNR and VNR-OH were 97.3° and 63.5°, respectively. After grafting with 3.70wt% organosilicon monomers such as methyltrimethoxysilane (MTMS), hexadecyltrimethoxysilane (HDTMS), 3-(trimethoxysilyl)propyl methacrylate (MPS) and methyltrichlorosilane (MTCS), the VNR-OH films grafted with MTCS (VNR-OH-MTCS) showed the highest water contact angle as 149°. When the VNR-OH-MTCS film was prepared by using various MTCS concentration (1-5 wt% in hexane), the water contact angle of VNR-OH-MTCS film increased to 155° when the MTCS concentration was 2 wt% in hexane. Whereas, the VNR film directly modified with the similar MTCS content showed the water contact angle as only 116°. This implied that the -OH functional groups were the effective active sites for reacting with MTCS and induced the obtained films having superhydrophobicity. In the application aspects, the VNR-OH-MTCS films exhibited antimicrobial activities to against the spread of gram-negative bacteria (E. coli) and grampositive bacteria (S.aureus) similar to VNR films resulting from the effect of the zinc compounds in the vulcanization. This indicated that the modification did not show the negative effect for anti-microbial activity of vulcanized rubber films. In addition, the VNR-OH-MTCS film could be applied as separation film for oil/water separation process with high separation efficiency of 98.6%.